Redéfinir la famille pour en faire partie. Les mobilisations des "Femmes Chefs de famille" (France, 1963-1982) - Fiona Friedli (Genre & Histoire)
In 1963, activists of a French pro-family union created the first Committees for women heads of household, which gathered together widows, divorcees and single mothers. This article draws on existing archives to depict the history of these activists between 1963 and 1982, as well as their mobilizations to improve and defend the rights of their families. At that time, these activists were legally excluded from any institutional representation with respect to public authorities, because of the first article of the Family Act, which only recognized as families those who were united by marriage. These mothers without husbands sought to change this definition of the family in order to exist within the pro-family movement. Through the study of this marginal group of activists, the article analyzes the shifting contours of the family as a legal and social movement as well as the relationship between family movements and the women’s movement during the 1970s in France.